y=ln (x-1)^3/(2x+3)

y'=3(1/x-1)-(2/2x+3)

y'=(3/x+1)-(2/2x+3) answer

Is this right? its a problem on a take home test and im just wondering if i got it right. If its not can you point out where.thx

Printable View

- Mar 31st 2010, 02:21 PMcalculusphobeCheck this pls
y=ln (x-1)^3/(2x+3)

y'=3(1/x-1)-(2/2x+3)

y'=(3/x+1)-(2/2x+3) answer

Is this right? its a problem on a take home test and im just wondering if i got it right. If its not can you point out where.thx - Mar 31st 2010, 02:23 PMmr fantastic
You can check it here: Wolfram|Alpha